حقليا على نبات الطماطة Agrotis ipsilon (Hufn.) ( Lepidoptera:Noctuidae) تقييم كفاءة بعض المبيدات الحشرية بطريقتي معاملة مختلفة ضد الدودة القارضة السوداء - طالب محمد علي مشتاق; حسن الفرطوسي علاء; سلمان حامد داود (University of Thi-Qar Journal of Science, 2011)
The study was conduct to evaluate the field efficacy for some Insecticides by two different treatment, there are Foliar and Soil application against the Black Cutworm Agrotis ipsilon in tomatoes field.Results demonstrated that their were different in the treatment efficacy,The Foliar application Overtop in reducing the infection ratio percentage compared with Soil application, also the results showed that the Match 5 EC was overtop in reducing the infection ratio from 21.9% before spraying to 2.2% after 14 days.About the soil application , Regent (Fipronil) 10G was Overtop in reducing infestation ratio from 19.1% to 17.1% after 14 days compared with the other insecticides usage in the soil application.